2009
DOI: 10.1063/1.3237243
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of cluster ions through a tandem accelerator of several stripper gases

Abstract: The transmissions of carbon cluster ion beams through a tandem accelerator using several stripper gases (He, N2, CO2, and SF6) with a terminal voltage of 2.5 MV were measured as a function of the gas pressure in investigating the most suitable gas for cluster ion acceleration. This resulted in it being demonstrated that the highest transmission could be obtained using the smaller size gas, i.e., helium displayed the best performance of the four gases used. In addition, the ratio of transmissions of C(n) with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In generally, to accelerate monatomic ion beams, we use nitrogen (N 2 ) gas as a stripper gas in the charge exchange section of the tandem accelerator. However, the transmission experiments conducted on several gaseous species for cluster ion incidence demonstrated that higher transmission could be achieved when smaller-sized gases is used, e.g., helium [26]. Therefore, helium gas is recommended as a stripper gas for the C 60 ion beams.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…In generally, to accelerate monatomic ion beams, we use nitrogen (N 2 ) gas as a stripper gas in the charge exchange section of the tandem accelerator. However, the transmission experiments conducted on several gaseous species for cluster ion incidence demonstrated that higher transmission could be achieved when smaller-sized gases is used, e.g., helium [26]. Therefore, helium gas is recommended as a stripper gas for the C 60 ion beams.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…The negative ions are stripped to positive ions upon colliding with the stripper gas in the charge exchange chamber, and the positive ones are reaccelerated toward the ground potential. A stripper gas of nitrogen generally used in a tandem accelerator is changed to that of helium when cluster ions are accelerated because the beam intensity of intact positive cluster ions increases [18]. A high-intensity C 60 ion beam of a hundred pico-ampere level at an energy of 6 MeV can be available using a helium stripper gas and is mainly supplied to develop a highly sensitive surface analysis by means of time of flight mass spectrometry.…”
Section: Three Electrostatic Acclerators and Their Ion Sourcesmentioning
confidence: 99%
“…cluster [18]. A high-intensity C60 ion beam of a hundred pico-ampere level at an energy of 6 MeV can be available using a helium stripper gas and is mainly supplied to develop a highly sensitive surface analysis by means of time of flight mass spectrometry.…”
Section: Three Electrostatic Acclerators and Their Ion Sourcesmentioning
confidence: 99%
“…The nonlinear effects of swift cluster ion beams, for instance, the nonlinear increase of secondary particle emission arising from a very high energy density deposited at the surface of the target, have been of interest in the area of beams interacting with matter [1,2]. The 3-MV tandem accelerator at the Takasaki Ion Accelerator for Advanced Radiation Application (TIARA) is one of the facilities in which studies on the generation of cluster ion beams and their application have been most actively carried out [3][4][5]. For instance, studies on the nonlinear cluster effect in inorganic materials [6], interaction with solids [7,8], and surface analytical techniques have been carried out [9], and recently, the very efficient negative fullerene ion source was successfully developed [10].…”
Section: Introductionmentioning
confidence: 99%